VERBAL AND NON-VERBAL SIGNS FOUND IN GARNIER MEN ADVERTISEMENTS - Ni Kadek Widya Putri; I Dewa Ayu Devi Maharani Santika; Desak Putu Eka Pratiwi (ID Solutions, 2021)
There are many signs used in advertisements in the forms of words, sentence, spoken sentences, image or colors. This signs support each other in order to deliver the meaning in an attractive way. But sometimes these signs interpreted unsuitably and arises different perspective in the meaning. Therefore, this study aimed to find out the verbal and non-verbal signs found in Garnier Men advertisements as well as their meaning. The process of collecting data was conducted by observation method in order to obtain detail information and note taking technique. The data were analyzed descriptive qualitatively by using the theory of semiotic proposed by Saussure (1983), theory of meaning proposed by Barthes (1967), and supported by theory color from Wierzbicka (1996). Through the analysis, it found that, the advertisements are composed by verbal and non-verbal signs. Both signs contain denotative and connotative meaning. The denotative meaning consisted of the name of products, ingredients, also functions of each product. Meanwhile, the connotative meaning consisted of the statement in the advertisement, the color, the background, also the models used in each advertisement that have hidden meaning. The advertiser tends to used black color as the background of the advertisements since black color is match with men imaginary that is powerful, elegance and black color show men’s masculinity.